Skeletal muscle adaptation to indirect electrical stimulation: divergence between microvascular and metabolic adaptations - Roger W. P. Kissane; David Hauton; Peter G. Tickle; Stuart Egginton (Experimental Physiology, 2023)
Abstract Exercise involves a complex interaction of factors influencing muscle performance, where variations in recruitment pattern (e.g., endurance vs. resistance training) may differentially modulate the local tissue environment (i.e., oxygenation, blood flow, fuel utilization). These exercise stimuli are potent drivers of vascular and metabolic change. However, their relative contribution to adaptive remodelling of skeletal muscle and subsequent performance is unclear. Using implantable devices, indirect electrical stimulation (ES) of locomotor muscles of rat at different pacing frequencies (4, 10 and 40 Hz) was used to differentially recruit hindlimb blood flow and modulate fuel utilization. After 7 days, ES promoted significant remodelling of microvascular composition, increasing capillary density in the cortex of the tibialis anterior by 73%, 110% and 55% for the 4 Hz, 10 and 40 Hz groups, respectively. Additionally, there was remodelling of the whole muscle metabolome, including significantly elevated amino acid turnover, with muscle kynurenic acid levels doubled by pacing at 10 Hz (P < 0.05). Interestingly, the fatigue index of skeletal muscle was only significantly elevated in 10 Hz (58% increase) and 40 Hz (73% increase) ES groups, apparently linked to improved capillary distribution. These data demonstrate that manipulation of muscle recruitment pattern may be used to differentially expand the capillary network prior to altering the metabolome, emphasising the importance of local capillary supply in promoting exercise tolerance.